Kunskapspolitik för ett hållbart samhälle - Ekström, Anders; Johannisson, Karin; Sörlin, Sverker (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
The article consists of a conversation about a book entitled Alltings mått: Humanistisk kunskap i framtidens samhälle (title in translation: The Measure of All Things: Humanities-Based Knowledge in the Future Society), which was published in the fall of 2012. The book critically discusses how contemporary research and higher education policies in Sweden and elsewhere have affected the development of the humanities and its role in society, arguing for a more integrated view on the politics of knowledge in the future.